Measuring walking behaviour in commuting to work: investigating the role of subjective, environmental and socioeconomic factors in a structural model. Issue 2 (2nd April 2020) - Hatamzadeh, Yaser; Habibian, Meeghat; Khodaii, Ali
ABSTRACT: Most walking-related travel behaviour studies have defined walking behaviour using a single measure of travel and have almost focused on single trips actually taken rather than entire tour. These studies usually neglect the mediating role and the indirect effect of explanatory factors on walking behaviour. This paper tries to understand the walking behaviour in work-tour(s) instead of work trips and presents a definition of walking behaviour using total time of walking and having at least one walking trip in work-tour(s) as two measures of travel simultaneously. Using data collected in the city of Rasht, Iran in 2015 from 432 working commuters, a structural equation model (SEM) was calibrated. Our findings indicate the necessity of addressing subjective factors in walking-related studies in addition to built environment characteristics and the importance of not ignoring the indirect effect of factors which can be quite misleading in interpreting the walking behaviour of commuters.